1958
DOI: 10.1177/004051755802800804
|View full text |Cite
|
Sign up to set email alerts
|

The Preparation and Properties of Partially Benzylated Cotton

Abstract: Ternary systems, such as alcohol. water, and sodium hydroxide, have been used in the pretreatment bath or have been added in fixed quantities to cotton prior to etherifi cation with benzyl chloride. Evidence has been obtained which supports an hypothesis that increased reagent solubility, coupled with control of the cellulose: sodacellulose equilibrium. can lead to essentially homogeneous cotton cellulose modifications. In addition, the experiments have resulted in the preparation of interesting fibrous cellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

1964
1964
1985
1985

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…l'ojyacrylaniides [271, however, were shown to cause some wet recovery improvement. It has also been shown in this lahoratory 2 ~ 10, 26,55 ] , that benzylated. ,B-propiolactoneor t-caprotactonetreated cotton, cyanoethylated cotton, and partially acetylated cotton likewise do not exhibit much wet crease, recovery improvement.…”
supporting
confidence: 63%
“…l'ojyacrylaniides [271, however, were shown to cause some wet recovery improvement. It has also been shown in this lahoratory 2 ~ 10, 26,55 ] , that benzylated. ,B-propiolactoneor t-caprotactonetreated cotton, cyanoethylated cotton, and partially acetylated cotton likewise do not exhibit much wet crease, recovery improvement.…”
supporting
confidence: 63%
“…For each lattice type the spectra are very similar, indicating that the substitution of aromatic groups on the cellulose apparently did not influence the location of the stable free radicals in the irradiated molecule. Even in the case where the aromatic group was cleaved from the cellulose molecule (benzyl cellulose, Figure 2C) during irradiation, the location of the -3 14 49 3 14 49 3 15 50 3 12 42 5 10 33 49 5 9 33 45 5 9 35 55 5 11 32 48 --- 8 The major peak was at about the free electron value. stable free radicals was not changed.…”
Section: Resultsmentioning
confidence: 99%
“…The method proposed by Klein et al. [8] was found to be better suited than others, as it ensured a uniform treatment of the fibers and the loss in strength was not comparatively large. However, as it was preferred to benzylate the samples at one stretch and not rebenzylate them, to get samples with DS nearer to 1, a higher initial molar ratio of NaOH to cellulose was employed instead of 2.01 used by Klein et al…”
Section: Introductionmentioning
confidence: 99%
“…They observed that benzylation began at active spots on the fiber surface and moved inwards from one growth layer to the next. Klein et al [8] studied the preparation and properties of partially benzylated cellulose with the aim of retaining the mechanical strength with increased yields by employing ternary systems. Following this, Creely et al [ 1 ] made an x-ray study of the partially benzylated cotton samples and proposed a unit cell for benzyl cellulose.…”
Section: Introductionmentioning
confidence: 99%